(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Small businesses are the lifeline for sustaining the economy of any nation with their significant contribution in GDP and employment generation. The most comprehensive definition of small business in India has been given by the Ministry of MSMEs with effect from July, 2020 which classifies MSMEs on the basis of investment as well as turnover. While the importance of MSME sector for the economy is irrefutable, the sector is not free from problems. A major inhibition to the growth of the sector is the “access to finance”. It has been attempted to find out what are some variables that influence borrowing experience of MSME borrowers. Borrowing experience related data were collected from 750 MSMEs across different districts of Assam with the help of a schedule. Ordinal regression has been attempted to develop models to predict contribution of various demographic and non-demographic variables to difficulty faced by the MSME borrowers in obtaining loan from banks. Factors found to be significant predictors in identifying various dimensions of problems faced while borrowing from banks by MSMEs include inter alia registration status, age of owner, type of scheme availed, location, age of the business, etc. Many newly setup start-up MSMEs can hardly produce any rosy track record as a pre-condition for institutional credit accommodation to prove their credit worthiness; to reduce the risk of lending by banks and to contain occurrence of NPAs.